Book review of "University Administration" - Lang, Daniel Wallace (Canadian Journal of Higher Education, 2021)
Eliot, Charles W. (1908). University Administration. Boston: Houghton-Mifflin, The Riverside Press. Pages: 296. n/a. Reprints: Bushnell Press (2008) Price: 25.95USD; Bibliolife (2009) Price: 40.85USD; Nabu Press (2010) Price: 42.45 CDN; Read Books (2015) Price: 38.56CDN; Palala Press (2015) Price: 34.95USD; Wentworth Press (2016) Price: 26.60USD.